Algorithms That Can Deny Care, and a Call for AI Explainability - Talia, Domenico; Talia, Domenico (Computer (Long Beach, Calif.), 2024)
Recent examples of negative use of big data and machine learning come from their use in health care decisions involving a large number of patients. These cases highlight the need for algorithm explainability to help us better understand how artificial intelligence works in solving problems so we can then evaluate its accuracy and effectiveness.